Managing Edaphic Stress Interactions for Sustainable Agriculture under Changing Climate - K. Sammi Reddy (Journal of the Indian Society of Soil Science, 2026)
It gives me an immense pleasure to place it on record my deep sense of gratitude to the council of Indian Society of Soil Science for giving me an opportunity to deliver a very prestigious 50th Dr. R.V. Tamhane memorial lecture under the aegis of Indian Society of Soil Science one of the oldest professional societies established in 1934 before independence of the country. I am really humbled for this opportunity on this occasion. Although I did not have the opportunity to see personally Dr. R.V. Tamhane but then stalwarts in the field of soil science talked very high about him and a memorial lecture was kept to pay a rich tribute to a visionary soil scientist in the year 1974 soon after he left for his heavenly abode. Looking to the contributions of Dr. Tamhane in the field of soil survey, soil genesis, soil conservation and soil testing, I chose to speak on the topic “Managing Edaphic Stress Interactions for Sustainable Agriculture under Changing Climate” which will be real tribute to him to whom maintaining better soil quality was very close to his heart.